Potential of minimally invasive procedures in the treatment of uterine fibroids: a focus on magnetic resonance-guided focused ultrasound therapy - Fischer K; McDannold NJ; Tempany CM; Jolesz FA; Fennessy FM (Dove Medical Press, 2015)
Krisztina Fischer,1–3 Nathan J McDannold,1 Clare M Tempany,1 Ferenc A Jolesz,1,† Fiona M Fennessy1,4 1Department of Radiology, 2Renal Division, 3Biomedical Engineering Division, Brigham and Women’s Hospital, 4Department of Radiology, Dana-Farber Cancer Institute, Harvard Medical School, Boston, MA, USA †Ferenc A Jolesz passed away on December 31, 2014 Abstract: Minimally invasive treatment options are an important part of the uterine fibroid-treatment arsenal, especially among younger patients and in those who plan future pregnancies. This article provides an overview of the currently available minimally invasive therapy options, with a special emphasis on a completely noninvasive option: magnetic resonance-guided focused ultrasound (MRgFUS). In this review, we describe the background of MRgFUS, the patient-selection criteria for MRgFUS, and how the procedure is performed. We summarize the published clinical trial results, and review the literature on pregnancy post-MRgFUS and on the cost-effectiveness of MRgFUS. Keywords: uterine fibroids, MRgFUS, focused ultrasound, minimally invasive treatment